What makes a high performance organization five validated factors of competitive advantage that apply worldwide - De Waal, André (Hawkhurst, Cranbrook, Kent Global Professional Publishing Ltd., 2012)
"In his book André de Waal gives many real-life examples from a variety of sectors including finance, retail, industry, ICT, high education and government, all illustrating the successful workings of the HPO framework in organizations worldwide. Also included are many interviews with HPO leaders at Microsoft, SABMiller, Svenska Handelsbanken, HP, Tata Steel, Umpqua Bank, Unilever and KLM Royal Dutch Airlines"--Jacket, page [2].
Chapter 1. Introduction: -- Starting the journey toward HPO -- Toyota: an HPO in crisis -- Umpqua Bank (USA): a passion for excellence -- Chapter 2 Foundations of the HPO: research that spans the world -- The bonus as hygiene factor: the role of reward systems in the HPO -- International bank (the Netherlands): management makes the difference -- Retail International Group (Europe/Asia/South America): learning from the 'best countries' -- Ministry of Local Governance and Social Affairs (Rwanda): working on HPO in government -- Chapter 3 Management Quality: without good management there is no -- Longfellow Benefits (USA): even a full-blown HPO can improve -- De Beers Marine (South Africa): dealing with the past through the HPO Framework -- Chapter 4 HPO factor 2 - Openness & Action Orientation: less communication, more dialogue 111 -- Vietnamese banking industry (Vietnam): identifying the HPO characteristics of an industry -- Iringa University College (Tanzania): improving through applying the HPO Framework -- Palestine Polytechnics University (Palestine Territories): working on HPO in difficult circumstances -- Chapter 5 HPO factor 3 - Long-Term Orientation: stakeholder thinking trumps shareholder management -- The myth of economic growth -- Creating HPO interactions with customers -- The relationship between Corporate Social Responsibility and the HPO Framework -- Two mining multinationals (Peru): using the HPO Framework for corporate social responsibility purposes -- Archway Marketing (USA): flipping the organizational pyramid to become HPO -- Chapter 6 HPO factor 4 - Continuous Improvement & Renewal: keep improving ... and be truly innovative -- Amanco Plastigama (Ecuador): emphasizing corporate social responsibility as part of HPO -- Two diamond companies (Europe): strengthening the value chain through HPO -- Temping Agency (Europe): looking internally for best ideas -- Chapter 7 HPO factor 5 - Employee Quality: without good employees the HPO can never be achieved -- Atrion Networking Corporation (USA): being HPO in inconspicuous surroundings -- South American College of Higher Education (South America): balancing growth with stability -- Nabil Bank (Nepal): achieving the sector's top position -- Chapter 8 The HPO transition process: make it happen -- Reasons for starting an HPO Diagnosis -- ATLAS Consortium (UK): creating a successful partnership -- The HPO Framework: guideline for mergers -- Grohe (the Netherlands): achieving success during times of crises -- Chapter 9 Benefits of the HPO Framework: it pays to use it.
Includes bibliographical references (pages 301-314) and index.
Keywords: Organizational effectiveness